Effet de la p'eriode de pollinisation manuelle sur la fructification de l'igname (Dioscorea rotundata Poir; Dioscoreaceae) en Cote d'Ivoire: Effect of the manual pollination period on the fruiting of yams (Dioscorea rotundata Poir; Dioscoreaceae) in Ivory Coast - Babayoko, Y.; Kouakou, A.M.; Dibi, K.E.B.; Ehounou, A.E.; Essis, B.S.; Nzue, B.; Kouassi, A.B.; Nguetta, A.S.; Adebola, P.O. (2019)
D. rotundata is the most popular species among consumers in Côte d'Ivoire. However, its production is stagnating due to the many constraints associated with its cultivation, particularly virus diseases. The use of improved varieties from sexual reproduction could effectively contribute to sustainable production. This work aimed to evaluate the crossing period in order to increase fruiting rates in this species. A total of 28 intra-specific crosses were carried out using 4 female and 7 male clones from the CNRA-Bouaké yam collection. Two time slots H1 (from 7:30 to 11:00) and H2 (from 11:00 to 13:30), selected for crossings, were compared to determine the optimal pollination period. Out of 30061 pollinated flowers, 2249 fruits were obtained i.e 7.48% with a variation range from 1.16 to 51.06% as the average fruiting rate depending on the clone combinations. Fruiting rates were significantly higher in H1 (8.53%) compared to 6.22% in H2. The female clone, Cnraigr09/00001, has recorded the highest fruiting rate especially in H1 (18.10%). Similarly, the male clones CIVCDr072, TDr00/00380 and TDr95/18555 have got the highest rates in H1 with 9.3; 9.8 and 16.3% respectively compared to those in H2. The couple Cnraigr09/00001 x TDr99/18555 recorded fruiting rates of 35.41% and 8.78% statistically different at schedule H1 and H2, respectively. A strong variation in the fruiting rate in favor of the H1 schedule was obtained between the different clone combinations.